Complete reactivation of X chromosomes from human chorionic villi with a switch to early DNA replication. - Migeon, B R (1986)
Mammalian sex-dosage compensation is mediated by maintaining activity of only one X chromosome. The asynchronous DNA synthesis characterizing the silent human X chromosome is thought to be reversible only during ontogeny of oocytes. We have previously shown that the glucose-6-phosphate dehydrogenase (G6PD) locus (G6PD) on the allocyclic X chromosome in chorionic villi is partially expressed. We now show that in hybrids derived from a clone of chorionic villi cells (heterozygous for G6PD A) and mouse A9 cells, the loci for G6PD, hypoxanthine phosphoribosyltransferase (HPRT) and phosphoglycerate kinase are expressed on both human X chromosomes; the human X chromosomes carrying either G6PD A or B replicate synchronously with each other and with murine chromosomes. The X chromosome with G6PD A was identified as the original late-replicating X, because methylation in the body of the HPRT gene on this chromosome remained characteristic of the inactive X chromosome. These results indicate that X-chromosome inactivation is completely reversible in cells of trophoblast origin; induction of full transcriptional activity is accompanied by acquisition of isocyclic replication, showing an intimate relationship between these processes. The molecular events responsible for this reversal may be similar to those occurring during maturation of oocytes. Chorionic villi and derivative hybrids provide in vitro models for exploring early events that program the single active X chromosome.